Complexities of Muslim Women Managers’ Careers: An Identity Perspective - Rossenkhan, Zubeida; Au , Wee Chan; K Ahmed, Pervaiz (2016)
Women in managerial positions continually narrate experiences of discrimination, stereotyping and several forms of career blocks limiting their advancement. Consequently underrepresentation of women and female talent drain remains a key issue as a result of these negative experiences. To sustainably address these issues to attract and retain female talent, it is essential to understand the specific experiences and unique challenges of women relative to their context. Although a number of studies have examined the differences between men and women routes to success, most studies fail to take into account the cultural differences that play a crucial role in shaping an individual’s subjective perceptions and overall experiences. Understanding the influence of the interactions between culture, religion and context on an individual’s identity will shed light to unique experiences of Muslim women managers in Malaysia. The research conducts in-depth interviews with top level Malay managers, probing their experience of upward career mobility and inequities in the workplace. The study uncovers what it essentially means to be a Muslim woman manager in Malaysia, the unique challenges these women face, and how Muslim women managers in Malaysia experience and manage their roles in the family, workplace and society in their attempt for career success.